Subcutaneous Injection of Tranexamic Acid to Reduce Bleeding During Dermatologic Surgery: A Double-Blind, Placebo-Controlled, Randomized Clinical Trial. Issue 6 (June 2019) - Zilinsky, Isaac; Barazani, Tami Brutman; Visentin, Denis; Ahuja, Kiran; Martinowitz, Uriel; Haik, Josef
Abstract : BACKGROUND: Topical application, oral, and IV injection of tranexamic acid (TXA) have been used to reduce surgical bleeding. OBJECTIVE: To evaluate the safety and efficacy of TXA injected subcutaneously to reduce bleeding during dermatologic surgery. METHODS: In this double-blinded, placebo-controlled, randomized prospective study, 131 patients were randomized to subcutaneous injection of lidocaine 2% diluted 1:1 with either saline (placebo) or TXA 100 mg/1 mL before surgery. Before the second stage or closure, size measurements of bloodstain impregnation on Telfa and surgical wound size were recorded and analyzed using mixed-effects linear regression. Subjective evaluation of hemostasis was performed using 4-point scale grading and analyzed using Fischer's exact test. RESULTS: One hundred twenty-seven patients completed the study. The bloodstain to surgical wound size ratio was smaller in the TXA group (1.77) compared with the placebo group (2.49) ( p < .001). An improved effect of TXA on bleeding was observed in the subgroup of patients receiving anticoagulants (mean difference; 95% confidence interval; −0.83; −1.20 to −0.46 p < .001). The subjective hemostasis assessment was significantly better in the TXA group overall ( p = .043) and anticoagulant subgroup ( p = .001) compared with the placebo group. CONCLUSION: Subcutaneous injection of TXA was safe, reduced bleeding during dermatologic surgery, and particularly effective for patients receiving anticoagulation treatment.